The contributions of Chinese anthropology: A conversation between Roberto Malighetti and Yang Shengmin - Malighetti, Roberto; Shengmin 杨圣敏, Yang (Anuac, 2017)
This article is the product of a long-term relationship between Prof. Yang Shengmin (Minzu University of China) and Prof. Roberto Malighetti (University of Milano-Bicocca). It is the outcome of a scientific collaboration that started in 2012 in Beijing, continued with the conference Anthropologies From in China. The First Italian Conference (University of Milano-Bicocca, 13.12. 2013), and was consolidated by the didactic activities at the Minzu University of China. It took the present form in the course of a conversation in the offices of the Collaborative Innovation Center for Ethnic Minority Development (Minzu University, Beijing) on the 6th of June 2016. Transcribed and then revised by both authors, the text considers the importance of Chinese anthropology and its contribution to the international dialogue. It probes the possibilities open to Chinese anthropology to offer an original articulation of its tradition with the Western influences that accompanied, from the very beginning, the development of anthropology in China. The Chinese innovative proposals are synthetized under three approaches: the historical, the Marxist, the applied, and the study of minorities.